Indeterminação social, teoria das organizações e decisão jurídica: observações Luhmannianas de um (des)encontro epistemológico contemporâneo - Azevedo, Guilherme de (Universidade do Vale do Rio dos Sinos, 2010)
This paper presents a proposal for observation of the relationship (in)exisisting between social uncertainty, organizational theory and legal decision. To do so, will adopt the theoretical thinking of the German sociologist Niklas Luhmannn, who work possessed developments in these three areas, thus facilitating the articulation and development. Initially, the research seeks to analyze the formation of the paradigm of social uncertainty, which arises during the twentieth century with the emergence of new constructivist epistemologies, that questioning the assumptions of the scientific model inherited from modernity. At this time it will seek to position the sociology of Niklas Luhmann as the first modern post-ontological theory and its relevance to the formation of a social theory complex enough to observe the shape of today's society. In the second part, it will expose the correlation between the formation of social organizations and the need for assimilation contexts highly contingent, that is, an attempt will be to defend the thesis luhmannian organizations to emerge as evolutionary acquisitions aimed at absorbing social uncertainty. This concept starts from the idea that social organizations are formed, and at the same time, enable processes of decision making. Finally, it will describe some of the main theories of legal decision, with the scope to demonstrate a possible mismatch between these epistemological support and contribution of organization theory. This way it will can prove the maintenance of many of the assumptions of methodological individualism in contemporary legal Comp's decision, and its disconnection from the advances offered by the sociology of organizations, particularly in the sense of Niklas Luhmann’s autopoietic.
Keywords: Indeterminação; Organização; Decisão; Sistema jurídico; Indeterminacy; Organization; Decision; Legal system; ACCNPQ::Ciências Sociais Aplicadas::Direito